Smartups : lessons from Rob Ryan's Entrepreneur America boot camp for start-ups - Ryan, Rob, 1948- (Cornell University Press, 2002)
"Building successful start-ups is never easy, and the changing economic climate has raised the stakes. It's time to get smart. This book teaches would-be entrepreneurs the skills to lead companies that will grow and succeed. Rob Ryan, a pioneer in the high-tech industry, founded Ascend Communications in 1989 and provided firms with the infrastructure to keep up with the rapid growth of the Internet." "In Smartups, Ryan focuses on methods for building a profitable, sustainable business. He emphasizes the importance of testing ideas on customers and making sure a product offers something new and important."--Jacket